Risk stratification by donor-derived cell-free DNA: a three-year single center study of kidney transplant outcomes from 257 patients - Mendel, Rhys; Jalal, Kabir; Liu, Lin; Huang, Ying; Wan, Cynthia; Zou, Eric; Sorci, Olivia; Mohib, Kanishka; Kareem, Samer; Tomaszewski, John E.; Von Visger, Jon R.; Quigg, Richard; et al. (Frontiers in Immunology, 2026)
BackgroundDonor-derived cell-free DNA is an established blood-based biomarker used to assess alloimmune activity after kidney transplantation.MethodsWe performed a retrospective study of 257 kidney transplant recipients that had at least one dd-cfDNA measurements during 3-year period. The primary aim was to assess the association between dd-cfDNA levels with graft function and survival. Secondary exploratory aims included examining the relationships between dd-cfDNA strata and biopsy-proven rejection, donor-specific antibodies, C4d deposition, and longitudinal eGFR trajectories. Patients were stratified by their highest dd-cfDNA measurement into three groups: <0.50%, 0.50–0.99%, and ≥1.0%.ResultsPatients categorized in the ≥1.0% dd-cfDNA group had increased rates of rejection, more severe histopathologic injury, and a higher prevalence of DSAs. With the ≥ 0.50-0.90% dd-cfDNA group having greater variability and decline in eGFR over the 3 year period. In exploratory multivariable modeling, higher dd-cfDNA strata were associated with a decline in graft function and survival.ConclusionsElevated dd-cfDNA levels were associated with adverse alloimmune and functional outcomes, including rejection, DSA positivity, and reduced graft survival (p=0.0071). A logistic regression model identified eGFR decline in the >1.0% group to predict long-term graft failure and patient survival (p=0.04). These findings support the clinical value of dd-cfDNA as a biomarker of alloimmune risk in kidney transplant recipients.